Porphyria cutanea tarda associated with HFE C282Y homozygosity, iron overload, and use of a contraceptive vaginal ring - Barton, James C. (J Community Hosp Intern Med Perspect, 2016)
Porphyria cutanea tarda (PCT) is characterized by decreased uroporphyrinogen decarboxylase activity in hepatocytes, uroporphyrin I and heptacarboxyl porphyrin III accumulation, photosensitivity dermatitis, and increased storage iron. In women, estrogen therapy, including oral contraceptives, postmenopausal hormone replacement, and tamoxifen for breast cancer treatment, is a risk factor for PCT. We report the case of a woman who presented with PCT, HFE C282Y homozygosity, and hepatic iron overload and was using a contraceptive vaginal ring containing ethinyl estradiol, an estrogen. We discuss this case in the context of characteristics of other persons with PCT, including common HFE mutations, iron overload, and estrogen exposure.